Nature Contemplation Toward the Essentialization of Sustainable Green Training (A Study of kitab al-Lama'at by Sa'id Nursi) - Muhammad Raffin Althafullayya; Abdul Samee Jessar; Saifullah; Chandra, Agus Firdaus; Nur, Afrizal (Journal of Islamic Management, 2026)
the global ecological crisis has exposed the limitations of the conventional Green Training which often relies on mechanistic and compliance based approach the global that fail to foster long-term intrinsic motivation. this study aims to formulate a spiritually essentialized green training model by integrating Badiusman Said Nursi ecotheology from Kitab al-Lamaat. using a qualitative library research explores the transformative potential of tafakkur alam (nature contemplation). Findings reveal that essentializing training through be concepts of tajalli (divine manifestation) and ubudiyyah iqlimiyyah (ecological servitude) shifts employee motivation drom external pressure to theocentric commitment. the study concludes thats viewing nature as a mirror of divine names provides a stronger ontological foundation than secular models. implications suggest that HRD praactitioners should incorporate reflective-spiritual practices, such as contemplation journals, into corporate curricula. this paradigm shift not only promotes sustainable pro-enviromental behavior beyond the workplace but also addresses the root cause of moral dissengagement in enviromental management.